Transcranial magnetic stimulation for schizophrenia. - Dougall, N; McIntosh, A; Ebmeier, K (2006)
This is the protocol for a review and there is no abstract. The objectives are as follows: To estimate the effects of TMS alone compared with sham TMS or with 'standard management' and any other comparison interventions in reducing psychotic symptoms associated with schizophrenia.